Effects of different sintering additives on the synthesis of γ-Y2Si2O7 powders. Issue 13 (October 2016) - Fan, Xingyu; Wang, Hongjie; Niu, Min; Su, Lei; Zhang, Dahai; Zhou, Jun; Fan, Jinpeng; Shi, Jianjun
Abstract: Pure γ-Y2 Si2 O7 powders were synthesized by the solid-liquid reaction method using Y2 O3 and SiO2 powders with Li2 O, MgO or Al2 O3 additives. The effects of the metallic ions Li +, Mg 2+ and Al 3+ on the synthesis process were systematically investigated by X-ray diffraction and differential scanning calorimetry. The chemical kinetics of the Y2 Si2 O7 synthetic process was calculated to illuminate the influences of the different metallic ions on the formation of silicate. The results indicate that the additives could effectively reduce the synthesis temperature by 100–300 °C. The apparent activation energy of the synthetic reaction was reduced by 79.75%, 65.16%, or 56.77% when 6 mol.% of Li2 O, MgO, or Al2 O3 was added, respectively, and the reaction rate was also significantly increased.